Conductive Fibrous Skeletons: Ultrahigh‐Energy‐Density Flexible Lithium‐Metal Full Cells based on Conductive Fibrous Skeletons (Adv. Energy Mater. 24/2021). Issue 24 (24th June 2021) - Kim, Seung‐Hyeok; Kim, Nag‐Young; Choe, Ui‐Jin; Kim, Ju‐Myung; Lee, Young‐Gi; Lee, Sang‐Young
Abstract : In article number 2100531, Young‐Gi Lee, Sang‐Young Lee and co‐workers present conductive fibrous skeletons (CFS) as a new electrode architecture strategy for ultrahigh‐energy‐density flexible lithium–metal battery (LMB) full cells. The conductive poly(ethylene terephthalate) nonwoven and heteronanomat act as a CFS for Li metal anodes and over‐lithiated layered oxide cathodes, respectively. The resulting CFS–LMB full cell provides improvements in the (cell‐based) gravimetric/volumetric energy densities (506 Wh kgcell −1 /765 Wh Lcell −1 ) and mechanical flexibility.